Cell Phone Vibration Education Through a Simulation Approach to Preventing Diabetic Foot Neuropathy Wounds - Sintawati Majid; Juhelnita Bubun; Siti Rahmani; Syaiful Syaiful; Nova Arwian (An Idea Nursing Journal, 2025)
Background: Effective prevention of diabetic neuropathy foot ulcers requires improved patient attitudes toward foot care and early self-detection. Conventional educational methods, such as in-room counseling, are often unsustainable and lack personalization. Objective: To evaluate the impact of mobile phone vibration-based education, delivered through a simulation approach, on attitudes toward preventing diabetic neuropathy foot ulcers in patients with diabetes mellitus. Methods: This quantitative study employed a one-group pretest-posttest design and was conducted from October 28 to November 12, 2025, at the Bangkala Community Health Center, Makassar City. Data were collected from 60 purposively sampled respondents using attitude questionnaires and neuropathy foot examinations utilizing mobile phone vibration. Results: Respondents demonstrated improved attitudes toward prevention, with the proportion in the positive attitude category increasing from 10/60 (16.7%) to 45/60 (75.0%), and the negative attitude category decreasing from 30/60 (33.3%) to 5/60 (8.3%). The Wilcoxon test indicated that education on mobile phone vibration had a significant effect (p=0.000) on attitudes toward preventing diabetic foot neuropathy. Conclusion: Education using mobile phone vibration can facilitate positive changes in attitudes toward preventing diabetic foot ulcers through diabetic neuropathy screening, thereby contributing to a reduction in diabetic foot ulcer complications. Future studies should be conducted with larger sample sizes.